2020
DOI: 10.22452/mojem.vol8no3.2
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Madrasah: Analysis of Managerial Skills, Learning Supervision, School Culture, and Teachers’ Performance

Abstract: The study of the effectiveness of madrasah has become the concern of Indonesia's education system to compete both nationally and internationally. This study belonged to a correlational research design to determine and measure the level of influence between variables, such as principals' managerial skills, supervision of learning, school culture, and teacher performance. This research was carried out at the Madrasah Aliyah Negeri (Islamic Senior High School) in Tulungagung, East Java, Indonesia. The research qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 45 publications
(59 reference statements)
5
15
0
4
Order By: Relevance
“…Keprofesionalan inilah yang akan bermuara pada pelaksanaan tugas yang optimal sehingga baiklah kinerja guru. Faktor-faktor lain yang ikut memberi pengarruh pada kinerja guru diantaranya iklim sekolah, psikologis guru, tingkat pendapatan, motivasi kerja, dan kemampuan manajerian kepala sekolah (Barrie & Walwyn, 2021;Mutohar & Trisnantari, 2020;Shakuna et al, 2016).…”
unclassified
“…Keprofesionalan inilah yang akan bermuara pada pelaksanaan tugas yang optimal sehingga baiklah kinerja guru. Faktor-faktor lain yang ikut memberi pengarruh pada kinerja guru diantaranya iklim sekolah, psikologis guru, tingkat pendapatan, motivasi kerja, dan kemampuan manajerian kepala sekolah (Barrie & Walwyn, 2021;Mutohar & Trisnantari, 2020;Shakuna et al, 2016).…”
unclassified
“…Good performance results are the result of appropriate behavior, especially wisdom in behavior, and effective behavior in accordance with the skills and competencies needed [6], [47]. Good and effective teacher performance will shape the school's work culture, thereby improving the quality of education and creating an effective school [42]. Furthermore Andriani, Kesumawati, and Kristiawan concluded that performance is the work of a person or organization by doing and producing Something, physical or non-physical according to instructions, functions and tasks based on knowledge, attitudes, skills, and motivation.…”
Section: Teacher Performancementioning
confidence: 99%
“…Terdapat tiga fungsi utama pengawasan atau supervise yaitu sebagai administratif, pendidikan, dan dukungan. Demikian pula, penulis lain telah membahas sifat pendidikan dari supervise (Hoque et al, 2020;Mutohar & Trisnantari, 2020). Baik supervisor maupun yang disupervisi mencatat pentingnya fungsi pendidikan.…”
Section: Hasil Dan Pembahasanunclassified